Exposures Moved from Work to Home as a Public Health Hazard - İsmail Bulgur; Birgül Piyal (İstanbul Medical Journal, 2021)

(untitled)
There are numerous occupational pollutants originating from a wide variety of industrial areas and working environments. These pollutants can be brought inadvertently from workplace to home in various ways and may negatively affect the health of household. In the literature, this situation was known as para-occupational exposures in the past but today it is referred as take-home exposures. In this review article; transport pathway, the diversity of take-home exposures, the population at risk and occupational security deficits were examined and precautions in reducing the take-home exposures were discussed. At the same time, take-home exposures were considered as an important public health problem and the contribution of social inequalities to the extent of the problem was also evaluated. It is aimed to help researchers to have a comprehensive view of take-home exposures and to support preventive efforts.